Seated versus standing position for maximization of performance during intense uphill cycling - Hansen, E. A.; Waldeland, H. (Journal of Sports Sciences, 2008)
It is not known whether the seated or standing position favours performance during intensive bouts of uphill cycling. The following hypotheses were therefore tested: (1) the standing position results in better performance at a high power output, while (2) the seated position is best at a moderate power output. We also assessed the seated-standing transition intensity, above which seated cycling should be superseded by standing cycling for maximization of performance. Ten male cyclists (mean age 27 years, s = 3; height 1.82 m, s = 0.07; body mass 75.2 kg, s = 7.0; VO2max 70.0 ml · kg-1 · min-1, s = 5.2) performed seated and standing treadmill cycling to exhaustion at 10% grade and at four power outputs ranging from 86% to 165% of their power output at maximal oxygen uptake (Wmax). Power output at maximal oxygen uptake was obtained during determination of VO2max. There was no difference in time to exhaustion between the two cycling positions at 86% of Wmax (P = 0.29). All participants performed best at the highest power output (165% of Wmax) when standing (P = 0.002). An overall seated-standing transition intensity of 94% of Wmax was identified. Thus, in general, cyclists may choose either the standing or seated position for maximization of performance at a submaximal intensity of 86% of Wmax, while the standing position should be used at intensities above 94% of Wmax and approaching 165% of Wmax.